Reduction of DOM fractions and their trihalomethane formation potential in surface river water by in-line coagulation with ceramic membrane filtration - Pharkphum Rakruam (2018)
This research was aimed at investigating the reduction of DOM fractions and their trihalomethane formation potential (THMFP) by in-line coagulation with 0.1 μm ceramic membrane filtration. The combination of ceramic membrane filtration with a coagulation process is an alternative technology which can be applied to enhance conventional coagulation processes in the field of water treatment and drinking water production. The Ping River water (high turbidity water) was selected as the raw surface water because it is currently the main raw water source for water supply production in the urban and rural areas of Chiang Mai Province. From the investigation, the results showed that the highest percent reductions of DOC, UV-254, and THMFP (47.6%, 71.0%, and 67.4%, respectively) were achieved from in-line coagulation with ceramic membrane filtration at polyaluminum chloride dosage 40 mg/L. Resin adsorption techniques were employed to characterize the DOM in raw surface water and filtered water. The results showed that the use of a ceramic membrane with in-line coagulation was able to most efficiently reduce the hydrophobic fraction (HPOA) (68.5%), which was then followed by the hydrophilic fraction (HPIA) (49.3%). The greater mass DOC reduction of these two fractions provided the highest THMFP reductions (55.1% and 37.2%, respectively). Furthermore, the in-line coagulation with ceramic membrane filtration was able to reduce the hydrophobic (HPOB) fraction which is characterized by high reactivity toward THM formation. The percent reduction of mass DOC and THMFP of HPOB by in-line coagulation with ceramic membrane filtration was 45.9% and 48.0%, respectively. © 2014 The Research Centre for Eco-Environmental Sciences, Chinese Academy of Sciences.